2010
DOI: 10.1186/1756-6614-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto thyroiditis is more frequent than expected when diagnosed by cytology which uncovers a pre-clinical state

Abstract: BackgroundOur Thyroid-Multidisciplinary Clinic is a large referral site for thyroid diseases. Thyroid biopsies are mainly performed for thyroid cancer screening. Yet, Hashimoto thyroiditis (HT) is being too frequently diagnosed. The prevalence of HT is reported as 0.3-1.2% or twice the prevalence of type 1 diabetes. However, the prevalence of HT confirmed by cytology is still uncertain. To evaluate different aspects of thyroid physiopathology including prevalence of Hashimoto's, a database of clinical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 26 publications
10
47
1
4
Order By: Relevance
“…1 The mean age at presentation was 40.4years which is similar to a study carried out by Staii et al 14 The cytological diagnosis of autoimmune thyroiditis ( fig. 3 &4) was made in 44.2% comprising 42 cases (24 lymphocytic thyroiditis and 18 Hashimoto thyroiditis).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…1 The mean age at presentation was 40.4years which is similar to a study carried out by Staii et al 14 The cytological diagnosis of autoimmune thyroiditis ( fig. 3 &4) was made in 44.2% comprising 42 cases (24 lymphocytic thyroiditis and 18 Hashimoto thyroiditis).…”
Section: Discussionsupporting
confidence: 71%
“…Hence, detection of autoimmune thyroiditis in nodular goitre becomes clinically significant. [15][16] As with other studies, 14 an important aspect of this study is that most patients with autoimmune thyroiditis were pre-menopausal females with high TSH levels. The risk of miscarriage, fetal and neonatal death increases with higher TSH levels.…”
Section: Discussionmentioning
confidence: 84%
“…The presence of HT in our study on histopathology result was 19,3 %. In the study of Staii et al the prevalence of HT diagnosed by cytology was13.4% (19). Prevalence of papillary thyroid microcarcinoma (PTMC) was higher in patient with HT than non HT 28,3% versus 7% with a In conclusion, the existing data provide inconsistent evidence favoring a causal relationship between HT and PTC.…”
Section: Discussionmentioning
confidence: 69%
“…In the UK, Tunbridge et al (35) reported an overall HT prevalence of 0.8%. However, diagnosis based fine needle aspiration biopsy study; the cytology of HT seems to be much more prevalent, at 13.4% (36). This difference may be partially explained by the fact that for diagnosing clinical HT, abnormally elevated TSH, low thyroid hormones (34,35) and the confirmatory presence of thyroid autoantibodies are usually accounted for.…”
Section: Clinical Manifestationmentioning
confidence: 95%